2014
DOI: 10.1097/hjh.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported alcohol intake is a better estimate of 5-year change in blood pressure than biochemical markers in low resource settings

Abstract: Self-reported alcohol use was strongly associated with a 5-year increase in BP in Africans with a low socio-economic status. This was not found for biochemical measures, GGT and %CDT. Self-reported alcohol intake could be an important measure to implement in primary healthcare settings in middle to low income countries, where honest reporting is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
6
18
1
Order By: Relevance
“…This highlights the urgency to address hypertension in low‐ and middle‐income countries where awareness, treatment, and control are poor . In agreement with our previous results, Lloyd‐Sherlock and colleagues indicate that excessive alcohol use is a particularly important health behavior relating directly to the development of hypertension in low‐ and middle‐income countries. Although proactive public health interventions at a population level are advocated to curb the hypertension epidemic, we need to understand why certain health behaviors, such as excessive alcohol use, are driving the hypertension epidemic.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This highlights the urgency to address hypertension in low‐ and middle‐income countries where awareness, treatment, and control are poor . In agreement with our previous results, Lloyd‐Sherlock and colleagues indicate that excessive alcohol use is a particularly important health behavior relating directly to the development of hypertension in low‐ and middle‐income countries. Although proactive public health interventions at a population level are advocated to curb the hypertension epidemic, we need to understand why certain health behaviors, such as excessive alcohol use, are driving the hypertension epidemic.…”
Section: Discussionsupporting
confidence: 90%
“…We and others have demonstrated that alcohol intake (self‐report or γ‐glutamyl transferase) predicts hypertension development in black South Africans with low socioeconomic status. Furthermore, the average consumption per drinker in sub‐Saharan Africa (19.5 L) is among the highest in the world .…”
mentioning
confidence: 73%
“…[34] Also similar to the previous literature, infrequent/moderate alcohol consumption was negatively associated with SBP and DBP[36], while more frequent alcohol consumption was positively associated with SBP and DBP. [37] These associations, while statistically significant, were relatively small when compared to the observed associations between age, cohort, and urbanicity with SBP and DBP. Lastly, in our sensitivity analysis, we found that BMI was positively associated with absolute SBP and DBP in men and women.…”
Section: Discussionmentioning
confidence: 77%
“…Although more investigations are needed, the contribution of lifestyle factors to the epidemic of hypertension in SSA is increasingly being clarified . Indeed, it is known that at least 27.5% of the population in Africa is physically inactive; more than 30% of adults are overweight or obese; and alcohol consumption adversely influences the BP levels of African populations . Although studies on sodium and potassium content of local foods are scarce in SSA, the few available findings have suggested the potentially important role of these factors in SSA .…”
Section: The Importance Of Lifestyle or Behavioral And Lifestyles Facmentioning
confidence: 99%
“…15 Indeed, it is known that at least 27.5% of the population in Africa is physically inactive; 16 more than 30% of adults are overweight or obese; 17 and alcohol consumption adversely influences the BP levels of African populations. 18 Although studies on sodium and potassium content of local foods are scarce in SSA, the few available findings have suggested the potentially important role of these factors in SSA. [19][20][21][22] Owing to nutrition transitions driven by industrialization and globalization, consumption of high sodium foods is increasing across SSA, and the spread of ready-made meals within global supermarket chains and fast-food restaurants is reinforcing these trends.…”
Section: The Importance Of Lifestyle or Behavioral And Lifestyles Facmentioning
confidence: 99%